Investigation of the protective effect of gel incorporating Eugenia jambolana leaf extract on 5-fluorouracil-induced oral mucositis: an animal study - BİNGÖL ÖZAKPINAR, ÖZLEM; ARICIOĞLU, FEYZA (My University, 2022)
Purpose The study aimed to evaluate the possible preventive effect of two concentrations (3 and 5% w/w) of Eugenia jambolana (EJ) extract against 5-FU-induced mucositis. Method Sixteen adult rats were separated into four groups: two control and two preventive groups. Animals in Groups 1, 2, and 3 were injected intraperitoneally with 60 mg/kg/day of 5-FU on Day 1 followed by 150 mg/kg/day on Day 5. The rats in Group 4 (negative control) were given physiological saline at the same times and doses. Furthermore, on the fifth day of the study, the cheek and sublingual mucosa were irritated by external superficial scratches using the tip of an 18-G needle, followed by the application 15 mu L of 20% acetic acid, after which 3 and 5% EJ w/w gels were applied topically for animals in Groups 2 and 3, respectively. Results The weight and the mucositis scores were recorded. Antioxidant and anti-inflammatory markers and biochemical tests were analyzed. Significant differences were found between the study groups in weight loss, clinical mucositis scores, mortality rates, and antioxidant and anti-inflammatory parameters. Conclusion The preventive effect of 3% gel was significant, with no mortality rate, making it an option for preventive strategies.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Onkoloji; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Oncology; ONKOLOJİ; Klinik Tıp; Klinik Tıp (MED); ONCOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Mucositis; Chemotherapy; Eugenia jambolana; Antioxidant; Anti-inflammatory; Gel; NF-KAPPA-B; OXIDATIVE STRESS; INTERLEUKIN-10; CHEMOTHERAPY; MANAGEMENT; PLASMA